Development of multiplex real‐time reverse‐transcriptase polymerase chain reaction assay for simultaneous detection of Zika, dengue, yellow fever, and chikungunya viruses in a single tube. Issue 11 (16th August 2018) - Wu, Wenhui; Wang, Jin; Yu, Nan; Yan, Juying; Zhuo, Zhihao; Chen, Mengyuan; Su, Xiaosong; Fang, Mujin; He, Shuizhen; Zhang, Shiyin; Zhang, Yanjun; Ge, Shengxiang; et al.
Abstract : Zika virus (ZIKV), dengue virus (DENV), chikungunya virus (CHIKV) and yellow fever virus (YFV) share the same mosquito vectors and have similar clinical manifestations early stage of infection. Therefore, simultaneously differentiating these viruses from each other is necessary. We developed a multiplex real‐time reverse‐transcriptase polymerase chain reaction (RT‐PCR) assay for the differentiation of these four viruses in a single tube. The linear range was established by regression analysis, and the R 2 value for each virus was ≥0.98, and the 95% lower limit of detection for each virus was as follows (copies/reaction): ZIKV‐Asian, 9; ZIKV‐Africa, 15; CHIKV, 11; DENV‐1, 19; DENV‐2, 13; DENV‐3, 24; DENV‐4, 36; and YFV, 17. Meanwhile, our multiplex real‐time RT‐PCR has a good consistency with the commercial singleplex assay. In summary, the developed assay can be effectively used for the diagnosis of ZIKV, DENV, CHIKV, and YFV infections. Highlights: 1. The one‐step simultaneousdetection of ZIKV, DENV, YFV and CHIKV in a single tube can be achieved. 2. The multiplex assay have a good consistency with the commercial simplex real time RT‐PCR kit. 3. The multiplex assay has a good sensitivity and specificity.